Neonatal mortality in culturally appropriate birth versus conventional birth at Hospital San Luis de Otavalo, Ecuador, 2017-2022 - Pacheco-Quintana, Carmen (2024)
Objective: To determine neonatal mortality indicators related to culturally appropriate birthsversus conventional births at Hospital San Luis de Otavalo during the period 2017-2022. Methods: The study had a quantitative, observational, retrospective, non-experimental approach. The population consisted of all neonates registered at the hospital during this period. Results: The overall neonatal mortality by type of birth was 41.7% in cases occurring in the operating room (asphyxia and prematurity) and at home (sepsis and prematurity), followed by 33.3% as a result of culturally appropriate birth (asphyxia, anencephaly, and cyanotic heart disease), while 25% occurred in conventional birth conditions (fetal demise, acute fetal distress, and prematurity). Conclusions: The trend of neonatal mortality is decreasing, with no significant differences between both birth modalities. All surveyed patients reported satisfaction with theculturally appropriate birth method.